The infusion of blockchain technology into the accounting methodology of electric power enterprises-operators of the distribution system - R. TSEBEN (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2023)
In modern business conditions, accounting is significantly influenced by the development of artificial intelligence, the Internet of Things, information and blockchain technologies. Processing of accounting data in electric energy enterprises – operators of the distribution system (hereinafter – DSO) takes place using information technologies, which corresponds to modern world trends. Blockchain technologies are constantly developing, there is a gradual transition from the use of blockchain in cryptocurrencies to other areas of human activity. Therefore, the study of the prospects for the development of accounting and the advantages of using new, more promising, blockchain technologies in the DSO is relevant.The purpose of the article is to study the influence of blockchain technologies on the accounting methodology of electric power enterprises-operators of the distribution system in the conditions of the post-war reconstruction of UkraineThe article is devoted to the influence of blockchain technologies on the accounting methodology of electric power enterprises-operators of the distribution system. The disadvantages of double recording are highlighted as a consequence of the principle of duality of the facts of economic processes, duality of the circulation of economic means and sources of their formation. Approaches to the implementation of triple entry in the economic literature are analyzed. Prospects for the development of blockchain technology in the energy sector are considered. The advantages of blockchain technologies in accounting for the implementation of investment programs and the development of the distribution system and the negative points that slow down the implementation of blockchain technology in the accounting of the DSO are revealed. A methodology for implementing DSO investment programs using triple blockchain recording is proposedOn the basis of the conducted research, it is possible to draw a conclusion about the prospects of using blockchain technologies in the accounting of the implementation of investment programs of the Ukrainian DSO in the conditions of the post-war recovery of Ukraine. Despite the negative points that hold back the implementation of blockchain technology in the accounting of the DSO, the need to strengthen the trust of investors in accounting data, the openness of accounting data and the increased informativeness of accounting indicate the obvious need for its application.